Prevalence, Antibiotic Susceptibility, and Molecular Typing of Staphylococcus aureus and Methicillin-resistant S. aureus (MRSA) among Domestic Animals in Dharan, Nepal - Rubina Katuwal; Manita Shyaula; Bigyan Shrestha; Saroj Babu Koirala; Hemanta Khanal (Nepal Journal of Biotechnology)
Staphylococcus aureus, a commensal bacterium found on the skin, skin glands, and mucous membranes of humans and animals. It affects the skin, soft tissues, bloodstream, and lower respiratory tract, causing diseases such as endocarditis, osteomyelitis, and generalized scalded skin disease in animals. This study investigates the prevalence and antibiotic susceptibility patterns of S. aureus and Methicillin-resistant S. aureus (MRSA) among domestic animals in Dharan, Nepal. A total of 320 skin swab samples were collected from various domestic animals, revealing a 12.5% prevalence rate of S. aureus. Strikingly, MRSA prevalence was notably high at 60% among the isolated S. aureus strains. Antimicrobial susceptibility testing unveiled widespread resistance to commonly used antibiotics, with notable exceptions such as vancomycin. Molecular analysis using the spa gene as a marker for strain typing detected its presence in a small subset of MRSA isolates, suggesting the possibility of human colonization and further underscoring the interconnectedness of animal and human health. Only 5% of the MRSA isolates carried the spa gene, confirmed by PCR and gel documentation in samples from buffalo skin swabs. The study highlights the importance of interdisciplinary collaboration between veterinary and human medicine sectors to address the growing threat of antimicrobial resistance. Overall, this research contributes valuable insights into the epidemiology of S. aureus infections in livestock and advocates for stringent hygiene practices, prudent antibiotic usage, and routine veterinary monitoring to mitigate the spread of MRSA and protect public health interests.